ChemInform Abstract: Thermal, Non‐Catalyzed Huisgen Cycloaddition for the Preparation of 4, 5‐Bis(trimethylsilyl)‐1H‐1, 2, 3‐triazoles. Issue 16 (28th March 2013) - Brisbois, Ronald G.; Bergan, Alexandra M.; Ellison, Aubrey J.; Griffin, Percy Y.; Hackbarth, Kent C.; Larson, Steven R.
Abstract A general protocol is reported for the synthesis of the title triazoles (III) via 1, 3‐dipolar cycloaddition of azides and bis(trimethylsilyl)acetylene.